The Students’ Perception of ChatGPT as a Tool in Writing Assignment at English Education Study Program, University of Baturaja - Andre Agustian; Mila Arizah; Merie Agustiani (Fakultas Keguruan dan Ilmu Pendidikan Universitas Baturaja, 2024)
This study explores the perceptions of students in the English Study Program at Baturaja University regarding the use of ChatGPT as a tool for writing assignments. The research employed a quantitative descriptive method using a survey design. A total of 56 students were selected through convenience sampling. Data were collected through a 20-item Likert-scale questionnaire focused on three main indicators: perceived usefulness, perceived ease of use, and trust or reliance on ChatGPT for grammar and writing accuracy. The findings revealed that the overall mean score was 3.95, indicating a positive perception. This was supported by a high proportion of favorable responses, with 41.16% of students selecting “Agree” and 31.90% selecting “Strongly Agree”, totaling 73.06% positive responses across all questionnaire items.Each indicator also reflected a positive result: Perceived Usefulness had a mean of 4.01 (76.79% positive), Perceived Ease of Use scored 4.02 (75.72% positive), and Trust/Reliance showed a mean of 3.83 (66.67% positive). These results indicate that students considered ChatGPT to be beneficial, easy to use, and fairly reliable in supporting their academic writing. Students reported that ChatGPT helped enhance their writing motivation, grammar understanding, confidence, and idea development. While some concerns were noted regarding dependence and occasional inaccuracies, overall, the findings highlight the potential of ChatGPT as a supportive and accessible digital tool in academic writing within English language education.